Climate adaptation and agriculture: Solutions to successful national adaptation plans - Kissinger, Gabrielle; Sova, Chase; Allassane, B; Maïga, IA; Benefor, DT; Nutsukpo, D.K.; Ky-Zerbo, AZ; Roth-Liehoun, C; King'uyu, S.M.; Orindi, VA; Rojas, E.; Rivera, J.L.; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The purpose of this brief is to share insights on agriculture and NAPs with national-level decision makers in developing countries and Least Developed Countries (LDCs), multilateral agencies, UNFCCC negotiators and donors. This brief explores how countries are overcoming the biggest challenges in developing NAPs, outlines examples of successful cross-sector adaptation planning, explores influence and leverage necessary for successful NAP processes, and offers specific recommendations.